2012
DOI: 10.1039/c2sm07119c
|View full text |Cite
|
Sign up to set email alerts
|

High-performance ion gel with tetra-PEG network

Abstract: † Electronic supplementary information (ESI) available: Synthesis, method and supplementary data for fitting parameters obtained from the VTF equation for ionic conductivity (Table S1), photographs of the ion gel (Fig. S1) and TGA (Fig. S2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
131
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(135 citation statements)
references
References 28 publications
3
131
1
Order By: Relevance
“…A self-standing PE membrane can be readily obtained by introducing either physical or chemical crosslinking points on the polymers. A polymer gel membrane swollen with ILs (called ion gels) was prepared by the in situ polymerization of vinyl monomers [31,32], by the cross-end coupling reaction of tetra-arm poly(ethylene glycol) [33], or by the self-assembly of ABA-type triblock copolymers where A and B are insoluble and soluble sequences, respectively [33][34][35][36].…”
Section: Resultsmentioning
confidence: 99%
“…A self-standing PE membrane can be readily obtained by introducing either physical or chemical crosslinking points on the polymers. A polymer gel membrane swollen with ILs (called ion gels) was prepared by the in situ polymerization of vinyl monomers [31,32], by the cross-end coupling reaction of tetra-arm poly(ethylene glycol) [33], or by the self-assembly of ABA-type triblock copolymers where A and B are insoluble and soluble sequences, respectively [33][34][35][36].…”
Section: Resultsmentioning
confidence: 99%
“…We investigated the CO2 permselectivity and solubility for the tetra-armed poly(ethylene glycol) (Tetra-PEG) [emim][Tf2N] ion gel 51) . The previous study reported that the gel is mechanically robust (the maximum breaking strength by compression reaches 18 MPa) and thermally stable (up to 300 ) even at 6 wt% polymer content 52) . Figure 5 shows the CO2 permeability and selectivity for the Tetra-PEG [emim][Tf2N] membrane (94 wt%-IL) and the [emim] [Tf2N] SILM as a function of temperature.…”
Section: Chemical Absorbentmentioning
confidence: 99%
“…Outstanding ionogels were produced by Fujii et al exhibiting very high ionic conductivities (7.7-8.5 mS cm -1 ) and tensile breaking strains (310%-380%), but low tensile strengths of just 15-33 kPa [18]. Although there are many reports of flexible solid ionogel electrolytes, few report high elastic mechanical properties, and, few have attempted to demonstrate their function in a stretchable electrochemical cell.…”
Section: Introductionmentioning
confidence: 99%
“…High compliance and flexible electrolytes have been prepared by forming polymer networks within a range of ionic liquids, and the resulting solids are referred to as ionogels [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation